Kapampangan folklore implications for teaching social studies in Pampanga and Tarlac high schools - Dizon, Lino L. 1960- (1986)
This study attempted to put in proper perspective the place of Kapampangan folklore in the educative process. It endeavors to present teaching resources from the content areas of Kapampangan folklore that will help enrich the Social Studies curriculum in the secondary schools of Pampanga and Tarlac.
Thesis (M.A.T.)--University of the Philippines, Diliman.
Vita.
Keywords: Social sciences (Secondary) -- Study and teaching; Folklore -- Pampanga